Water Saturated Layer Beneath Volcano and its Implications to Volcanic Activity - T. Kagiyama (Indonesian Journal of Physics, 2004)
In recent years, a low resistive layer has been revealed by magneto-telluric surveys beneath some volcanoes in Japan. This layer is interpreted to be saturated by water, or altered by hydrothermal activity. The influence of underground water is important for volcanic activity, because many precursors of volcanic eruptions occur by an interaction of magma or volcanic gas and underground water, and a style of volcanic eruptions is controlled.